2007
DOI: 10.1007/s10238-007-0126-y
|View full text |Cite
|
Sign up to set email alerts
|

Impulse oscillometry: an alternative modality to the conventional pulmonary function test to categorise obstructive pulmonary disorders

Abstract: Impulse oscillometry (IOS) was introduced as an alternative modality to the conventional pulmonary function test (cPFT) to test lung mechanics. The objective of this study is to assess the use of IOS as an alternative, or in conjunction with cPFT, to categorise an obstructive respiratory disorder as chronic obstructive pulmonary disease (COPD) or asthma. Patients referred to the PFT laboratory, with different diagnoses of obstructive airways disorders, completed a standardised respiratory questionnaire prior t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 36 publications
4
35
0
5
Order By: Relevance
“…In this study, FVC, FEV 1 , FEV 1 /FVC, and MMEF decreased in COPD patients compared with healthy controls, which reflected airflow limitations. Among the IOS parameters, Z5, Fres, R5, R20, and R5–R20 increased significantly, and the degree of R5–R20 increase was much higher than the degree of R20 increase, which suggested that in COPD, the increase in peripheral airway resistance was predominant with a certain degree of increase in central airway resistance; this was consistent with other research results 1517. Under physiological conditions, the ratio of peripheral airway resistance to total airway resistance was 10%–25%, but in COPD patients, the percentage of peripheral airway resistance was greatly increased 14.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, FVC, FEV 1 , FEV 1 /FVC, and MMEF decreased in COPD patients compared with healthy controls, which reflected airflow limitations. Among the IOS parameters, Z5, Fres, R5, R20, and R5–R20 increased significantly, and the degree of R5–R20 increase was much higher than the degree of R20 increase, which suggested that in COPD, the increase in peripheral airway resistance was predominant with a certain degree of increase in central airway resistance; this was consistent with other research results 1517. Under physiological conditions, the ratio of peripheral airway resistance to total airway resistance was 10%–25%, but in COPD patients, the percentage of peripheral airway resistance was greatly increased 14.…”
Section: Discussionsupporting
confidence: 90%
“…Testing was performed using the Jaeger MasterScreen-IOS system (Carefusion Technologies, San Diego, CA, USA). The method has been described in detail elsewhere [19, 20]. In short, pressure impulses were sent from a loudspeaker through the respiratory system.…”
Section: Methodsmentioning
confidence: 99%
“…COPD and asthma studies have shown that IOS measurements are more sensitive than forced expiratory volume in 1 sec (FEV1) for measuring the pulmonary effects of bronchodilator drugs (13)(14)(15). Additionally, IOS measurements can also be used to sensitively diagnose obstructive lung disease (16,17). Thus, the understanding of which IOS measurements are correlated with the degree of airflow obstruction (as measured by FEV1) and which measurements are correlated with the degree of hyperinflation (measured by lung volumes) is required.…”
Section: Introductionmentioning
confidence: 99%